2021
DOI: 10.1007/s12010-021-03675-w
|View full text |Cite
|
Sign up to set email alerts
|

Biogas and Volatile Fatty Acid Production During Anaerobic Digestion of Straw, Cellulose, and Hemicellulose with Analysis of Microbial Communities and Functions

Abstract: BackgroundAnaerobic digestion (AD) is a promising method for straw treatment, but the complex composition and structure of straw limit AD e ciency and methane production. The main biodegradable components of straw are cellulose and hemicellulose. Because of the different chemical structures and physicochemical properties, the performance of AD of cellulose and hemicellulose is different, thus it's also different from that of straw. Research on the similarities and differences of AD of straw, cellulose and hemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Cellulose and hemicellulose digestibility is closely related to NDF and ADF digestibility because hemicellulose is part of the fiber fraction. Liu et al (2022) indicated that the digestibility of NDF and ADF is positively correlated with hemicellulose digestibility; as the digestibility of NDF and ADF increases, so does the digestibility of hemicellulose. Despite the fact that the T4 treatment contains higher lignin levels, this difference is not statistically significant when compared to the T1, T2, or T3 treatments.…”
Section: Effect Of Treatment On Hemicellulose and Cellulose Digestibi...mentioning
confidence: 99%
“…Cellulose and hemicellulose digestibility is closely related to NDF and ADF digestibility because hemicellulose is part of the fiber fraction. Liu et al (2022) indicated that the digestibility of NDF and ADF is positively correlated with hemicellulose digestibility; as the digestibility of NDF and ADF increases, so does the digestibility of hemicellulose. Despite the fact that the T4 treatment contains higher lignin levels, this difference is not statistically significant when compared to the T1, T2, or T3 treatments.…”
Section: Effect Of Treatment On Hemicellulose and Cellulose Digestibi...mentioning
confidence: 99%
“…Acetic acid is known to be the primary carbon source for biomethanation through AD. Most of the other VFAs, such as propionic acid, are also transformed into acetic acid before microbes incorporate them into the methane metabolism [67]. Under standard conditions, the transformation of certain VFAs, like propionate and butyrate, towards acetate, H2, and CO2 requires energy absorption, rendering it challenging to happen without external aid during AD.…”
Section: Factors Causing Vfa Accumulationmentioning
confidence: 99%
“…Being a vital component in the methanogenic process by serving as substrates, VFAs are positively linked to methane generation, when their concentration remains within a particular range. However, it is important to note that excessive aggregation of VFAs can have an inhibitory effect on AD, ultimately leading to system failure [67]. There is a number of factors accountable for VFA accumulation, mainly linked to turbulences in the conditions of AD [26].…”
Section: Factors Causing Vfa Accumulationmentioning
confidence: 99%
“…The high cellulose and hemicellulose content of EFB makes it a suitable feedstock for biogas production through anaerobic digestion. The energy potential of EFB is estimated to be 2.6-2.8 GJ/ton [4]. If all the EFB generated from palm oil mills in Indonesia, Malaysia, and Thailand were used for biogas production, it could potentially generate 38-41 million m³ of biogas per year, equivalent to 22-24 million GJ of energy (calculated based on a biogas yield of 500 m³/ton EFB and an energy content of 22 MJ/m³).…”
Section: Introductionmentioning
confidence: 99%